Soviet Policy Toward Siberian Native People: Integration, Assimilation or Russification? - Bartels, Dennis; Bartels, Alice (Culture, 1986)
During eight months in 1981-82, we collected data on the occupations, educational attainments, and ethnicity of 58 Siberian Native academics, professionals, and students, and their immediate family members. We have attempted to use our data, and the conclusions of other Soviet and Western researchers on Soviet nationalities policy, to determine whether the concepts of structural integration, cultural integration, assimilation and Russification, as sometimes used by North American social scientists. accurately characterize the results of Soviet policy toward Siberian Native People. It is argued that these concepts are inadequate for this task.